Arabidopsis vacuolar H+-ATPase subunit E isoform 1 is required for Golgi organization and vacuole function in embryogenesis - Strompen, Georg; Schumacher, Karin (The plant journal, 2005)
Vacuolar H+-ATPases play an important role in maintaining the pH of endomembrane compartments in eukaryotic cells. The functional relevance of this homeostasis for multicellular development has not been studied in plants. Here, we analyze the biological consequences resulting from the lack of subunit E isoform 1 (VHA-E1) encoded by the Arabidopsis TUFF gene. tuff mutant embryos are lethal, displaying variably enlarged cells with multiple nuclei, large vacuoles containing inclusions, abnormal organization of Golgi stacks, and cell wall defects. Rescue of embryo lethality by cell cycle-regulated expression of VHA-E1 results in abnormal seedlings with non-functional meristems and defective cell differentiation. VHA-E1 is the predominant isoform in embryogenesis whereas VHA-E3 is expressed mainly in the endosperm and surrounding maternal tissues during seed development, and VHA-E2 is pollen-specific. VHA-E1 protein accumulates at endomembrane compartments including vacuoles and endosomes, but appears absent from the plasma membrane. Our results suggest an essential role for VHA-E1 in maintaining a functional secretory system during somatic development but not in the haploid gametophytes.